Boron nitride-based materials for water purification: Progress and outlook. (January 2021) - Ihsanullah, Ihsanullah
Abstract: Analogous to the carbon family, boron nitride (BN)-based materials have gained considerable attention in recent times for applications in various fields. Owing to their extraordinary characteristics, i.e., high surface area, low density, superior thermal stability, mechanical strength, and conductivity, excellent corrosion, and oxidation resistance, the BN nanomaterials have been explored in water remediation. This article critically evaluates the latest development in applications of BN-based materials in water purification with focus on adsorption, synthesis of novel membranes and photocatalytic degradation of pollutants. The adsorption of various noxious pollutants, i.e., dyes, organic compounds, antibiotics, and heavy metals from aqueous medium BN-based materials are described in detail by illustrating the adsorption mechanism and regeneration potential. The major hurdles and opportunities related to the synthesis and water purification applications of BN-based materials are underscored. Finally, a roadmap is suggested for future research to assure the effective applications of BN-based materials in water purification. This review is beneficial in understanding the current status of these unique materials in water purification and accelerating the research focusing their future water remediation applications. Graphical abstract: Image 1 Highlights: A comprehensive overview of BN-based materials in water treatment is presented. The potential of various BN structures in adsorption, membrane separations and photocatalytic degradation is evaluated. The major challenges in the water purification applications of BN-based materials are accentuated. A roadmap for future research is suggested.